PERAN FORUM KERUKUNAN UMAT BERAGAMA (FKUB) DALAM MENYELESAIKAN KONFLIK PENDIRIAN RUMAH IBADAH DI ASIA MEGA MAS - Fitriani Fitriani; Khoirul Azhar Siregar (Studia Sosia Religia, 2021)
Conflict is a phenomenon that often occurs in society. Be it conflicts over religious nuances or conflicts regarding social and culture, likewise with the phenomenon that occurred at the Amal gathering mosque on asia street. There is a plan demolish the mosque, conflik can usually be resolved by means of deliberation by summoning traditional leaders. Relegius, leader and local government officials, and summoning mass organizations so that they can mdiate between those in conflict.Bath from the government and the police, and the religious hormony forum. The goal is so that conflict does not occur prolongend which wiil relult in bloods shed. The method, with the sociology of conflict approach is an approach to seeing the reality of how phenomena occur in the community and seeing how life is. From this researcher, the researcher knows how the eerly history of the conflict in the establish ment of houses of worship on jalan asia. The asia mega mas complex. And how the religious harmony forum deals with conflicts over eviction of houses of worship, and what are the inlibiting factor in resolving conflict is over the construction of houses of worship. As for the results achieved in resolving conflicts over the construction of houses of worship, namely by making reconciliation between the local community and the state enterprise so that there is no prolonged conflict which wiil result in prolonged en mity.